Parameters That May Be Used for Predicting Failure during Endoscopic Retrograde Cholangiopancreatography. (3rd June 2013) - Balik, Emre; Eren, Tunc; Keskin, Metin; Ziyade, Sedat; Bulut, Turker; Buyukuncu, Yilmaz; Yamaner, Sumer
Abstract : Aim . Endoscopic retrograde cholangiopancreatography (ERCP) is frequently used for the diagnosis and treatment of hepatic, biliary tract, and pancreatic disorders. However, failure during cannulation necessitates other interventions. The aim of this study was to establish parameters that can be used to predict failure during ERCP. Methods . A total of 5884 ERCP procedures performed on 5079 patients, between 1991 and 2006, were retrospectively evaluated. Results . Cannulation was possible in 4482 (88.2%) patients. For each one-year increase in age, the cannulation failure rate increased by 1.01-fold (P = 0.002 ). A history of previous hepatic biliary tract surgery caused the cannulation failure rate to decrease by 0.487-fold (P < 0.001 ). A tumor infiltrating the ampulla, the presence of pathology obstructing the gastrointestinal passage, and peptic ulcer increased the failure rate by 78-, 28-, and 3.47-fold, respectively (P < 0.001 ). Conclusions .Patient gender and duodenal diverticula do not influence the success of cannulation during ERCP. Billroth II and Roux-en-Y gastrojejunostomy surgeries, a benign or malignant obstruction of the gastrointestinal system, and duodenal ulcers decrease the cannulation success rate, whereas a history of previous hepatic biliary tract surgery increases it. Although all endoscopists had equal levels of experience, statistically significant differences were detected among them.